استخدام طريقة المحاورة في تعليم مهارة الكلام على الطلاب بمعهد زين الحسن قنقون - Muh. Rokhm Maulana; Mamluatun Ni'mah; Shobirin Shobirin (ANWARUL, 2025)
This study examines the implementation of the muhāwarah method in teaching Arabic speaking skills at Ma'had Zainul Hasan Genggong. The research is motivated by the need for a method that enhances students’ active fluency in spoken Arabic within an immersive environment. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation. The findings indicate that the muhāwarah method is applied through five stages: guided group reading with the teacher, translation, speaking practice, material development, and the execution of Arabic Language Day activities. This method has been shown to positively contribute to improving students’ speaking abilities. However, challenges remain for beginner students who struggle to comprehend and mimic Arabic conversations. The study recommends integrating the muhāwarah method with other approaches to address these limitations.